2017
DOI: 10.1371/journal.pone.0184306
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine induced epigenetic transgenerational inheritance of disease, lean phenotype and sperm epimutation pathology biomarkers

Abstract: Ancestral environmental exposures to a variety of environmental toxicants and other factors have been shown to promote the epigenetic transgenerational inheritance of adult onset disease. The current study examined the potential transgenerational actions of the herbicide atrazine. Atrazine is one of the most commonly used herbicides in the agricultural industry, in particular with corn and soy crops. Outbred gestating female rats were transiently exposed to a vehicle control or atrazine. The F1 generation offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(173 citation statements)
references
References 88 publications
(157 reference statements)
11
161
0
1
Order By: Relevance
“…Previous studies found an increased susceptibility to obesity in F3 generation rats ancestrally exposed to the pesticide DDT, and an increase in a lean phenotype in the F3 generation rats ancestrally exposed to the herbicide atrazine [36,37]. The present study investigated whether there were common DMR and associated genes between the control, DDT, and atrazine lineage male and female adipocytes in order to identify potential novel gene pathways modulated by DNA methylation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies found an increased susceptibility to obesity in F3 generation rats ancestrally exposed to the pesticide DDT, and an increase in a lean phenotype in the F3 generation rats ancestrally exposed to the herbicide atrazine [36,37]. The present study investigated whether there were common DMR and associated genes between the control, DDT, and atrazine lineage male and female adipocytes in order to identify potential novel gene pathways modulated by DNA methylation.…”
Section: Discussionmentioning
confidence: 93%
“…No sibling or cousin breeding were used in either generation in order to avoid inbreeding depression of epigenetics or artifacts. The F3 generations were not exposed directly to DDT or atrazine in order to see transgenerational effects as previously described [36,37]. All generations of the control, atrazine, and DDT rats were given the same lighting, food, and water conditions.…”
Section: Animal Studies and Breedingmentioning
confidence: 99%
See 2 more Smart Citations
“…As reviewed in Ref. , there are data for transgenerational inheritance of diseases/dysfunctions including reproduction, obesity, psychiatric disorders from a variety of environmental stressors including vinclozolin, bisphenol A, atrazine bisphenol A plus phthalates (DEHP and DBP), permethrin plus DEET, methoxychlor, Jet fuel 8, phthalate (DEHP),dioxin, DDT, PCBs, tributyltin, nicotine, alcohol, calorie restriction, high‐fat diets, folate and stress. Mechanisms currently focus on a variety of epigenetic changes including DNA methylation, histone changes and non‐coding RNAs .…”
Section: Transgenerational Inheritancementioning
confidence: 99%